Impacto do manejo da talhadia e alto fuste na qualidade da madeira de eucalipto - Cirilo, Nauan Ribeiro Marques (2023)
Coppicing is a management system that has been widely studied due to the productive and economic advantages it provides to forestry plantations, therefore, it is ideal to identify the impact that this management has on the quality of the wood. The objective of this work was to evaluate the differences in growth and wood quality of ten Eucalyptus genotypes, at three years of age, conducted simultaneously under high forest and coppice regimes, in addition to the quantity of stems managed. For this, six trees per clone were sampled in both regimes, and in the coppice, three trees with one stem and three trees with two stems were collected. Wood and bark basic density and its variation from base-to-top direction, estimated biomass per tree, pith eccentricity, and percentage of heartwood and bark were evaluated. The properties of wood and bark were submitted to individual variance analysis and the averages of the management regimes (high forest and coppice) were compared by using the Scott Knott test (α = 5%). Only the G13 clone showed a statistical difference for the basic wood density, being the highest value in coppice management conducted with two stems, where it presented a greater range of variation for eight of ten clones. Four clones showed statistical differences among managements for the percentage of heartwood. Trees that grew under coppice produced more heartwood, excepted for the clone G5, which produced more heartwood in the high forest management. Considering the average pith eccentricity of the trees, five clones differed statistically, and coppice with two stems was the treatment that showed the greatest eccentricity. When compared to the high forest regime, nine coppice clones with two stems presenting higher average values for the same characteristic. All wood properties did not show significant differences between high forest and coppice managements, for eucalyptus clones evaluated at three years of age, except for the pith eccentricity which was greater for coppice when conducted with two stems.